Etika Bermedia Sosial: Peningkatan Pemahaman Penggunaan Media Sosial Dalam Membangun Generasi Yang Bertanggung Jawab - Syarifuddin; Andika Marsuki; Nursalim Nursalim; Ibrahim; Sidrah Afriani Rachman (JURPIKAT, 2026)
This Community Service (PKM) activity aims to improve understanding and ethics in the use of social media as an effort to foster a responsible generation among students. This activity was carried out online via Zoom Cloud Meeting, involving students at Campus VI of the Elementary School Teacher Education Program, Faculty of Education, Makassar State University. Based on the results of the pre-test and post-test, there was a significant increase in participants' understanding of the appropriate and responsible use of social media, as well as their awareness of the importance of implementing ethics in interacting on social media. This activity successfully increased the understanding and ethics of social media use in fostering a responsible generation. This program is expected to serve as a reference or model in efforts to improve social media literacy and ethics among students in facing the dynamics of communication in the digital era.